Physical education of preschool children forms of trainin - A.Abdullaev; F.Boqiev (Genius Journals, 2022)
Theoretical and analytical material on the problems of professional theoretical and practical training of bachelors in the field of physical education for preschoolers and ways to solve them. Preschool education is designed for bachelors, masters and many specialists of educational institutions.
Keywords: Physical Exercise; Education; Government Program; Agenda